2003
DOI: 10.1097/00126334-200311010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Antiretroviral Adherence for Patients Living with HIV Infection and AIDS in Botswana

Abstract: ARV adherence rates in this study were comparable with those seen in developed countries. As elsewhere, health care providers in Botswana were often unable to identify which patients adhere to their ARV regimens. The cost of ARV therapy was the most significant barrier to adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
354
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(394 citation statements)
references
References 24 publications
31
354
9
Order By: Relevance
“…Finally, the association between end-user cost and adherence confirms observations from Senegal (Laniece et al, 2003), Uganda (Byakika-Tusiimi et al, 2005) and Botswana (Weiser et al, 2003;WHO, 2005b). Lack of compliance has immediate implications for the development of resistance to first-line ART regimens and leads to increased costs in the future, as second-line regimens cost five to ten times more than first-line regimens.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, the association between end-user cost and adherence confirms observations from Senegal (Laniece et al, 2003), Uganda (Byakika-Tusiimi et al, 2005) and Botswana (Weiser et al, 2003;WHO, 2005b). Lack of compliance has immediate implications for the development of resistance to first-line ART regimens and leads to increased costs in the future, as second-line regimens cost five to ten times more than first-line regimens.…”
Section: Discussionsupporting
confidence: 78%
“…Provision of no-cost therapy to all eligible HIV-infected individuals in the household ensured sustained adherence. As has been reported in other studies (Mills et al 2006a;Nachega et al 2004;Weiser et al 2003), perceived stigma was commonly reported as a barrier to access and adherence to ART.…”
Section: Qualitative Findingssupporting
confidence: 72%
“…While most studies have shown high levels of adherence to ART in resource-constrained settings Bisson et al 2008;Byakika-Tusiime et al 2005;Diabate et al 2007;Etard et al 2007;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Mills et al 2006b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;San Lio et al 2008;Tadios and Davey 2006;Weidle et al 2002;Weidle et al 2006;Weiser et al 2003) there has been little discussion about how HIV? women balance the demands of adherence to HIV ART, childcare, and antiretroviral adherence among their children who are HIV-infected.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity is one of the multiple barriers that individuals face in initiating and adhering to long-term medical therapies such as ART and DOTS, especially in resourcelimited settings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Other patient-related barriers include the complexity of the medication regimen [18], emotional distress [7], illness costs to households [19], stigma [20], health beliefs and poverty [4], limited knowledge of the disease [21], difficulty remembering [22], intentional non-adherence due to adverse drug reactions [23] and harmful use of alcohol [24].…”
Section: Introductionmentioning
confidence: 99%